Against the Evils of Democracy: Fighting Forced Disappearance and Neoliberal Terror in Mexico - Wright, Melissa W. (Annals of the American Association of Geographers, 2018)
On 26 September 2014, Mexican police forces in Iguala, Guerrero, attacked and abducted four dozen students known as normalistas (student teachers); some were killed on the spot and the rest were never seen again. Within and beyond Mexico, rights activists immediately raised the alarm that the normalistas had joined the country's growing population of "the disappeared," now numbering more than 28,000 over the last decade. In this article, I draw from a growing scholarship within and beyond critical geography that explores forced disappearance as a set of governing practices that shed insight into contemporary democracies and into struggles for constructing more just worlds. Specifically, I explore how an activist representation of Mexico's normalistas as "missing students" opens up new political possibilities and spatial strategies for fighting state terror and expanding the Mexican public within a repressive neoliberal and global order. I argue that this activism brings to life a counterpublic as protestors declare that if disappearance is "compatible" with democracy, as it appears to be within Mexico, then disappeared subjects demand new spaces of political action. They demand a countertopography where the disappeared citizens of Mexico make their voices heard. Activists demonstrate such connections as they compose countertopographies for counterpublics across the Americas landscape of mass graves, prisons, and draconian political economies, mostly constructed in the name of democracy and on behalf of securing citizens. Understanding how Mexico's activists confront the intransigent problems of state terror, spanning from dictatorships to democracies, offers vital insights for struggles against policies for detaining and disappearing peoples there and elsewhere in these neoliberal times.